Turbulence and Related Phenomena - Barillé, Régis (IntechOpen, 2019)
This book presents some of the most important results concerning atmospheric turbulence and some of its effects on the propagation of a light beam. Atmospheric turbulence causes fluctuations in both the intensity and the phase of the beam and still must be understood and modelized for applications in photonics or environmental metrology. The future of free-space optical (FSO) communication through atmospheric turbulence channels is especially of interest and research on high bit-rate communications attracts more and more interest as an alternative to radio links because of bandwidth, spectrum, and security issues. Some of the current solutions for improving FSO communications are presented in this book.